Identification of the T-box transcription factor t-bet in chickens and its role in immune response - Yuxin Guo; Zhaocan Zhou; Hui Gao; Shujun Zhang; Zhi Chen; He Chang; Hong Cao; Li Gao; Yongqiang Wang; Shijun J. Zheng (Poultry Science, 2025)
T-bet (T-box transcription factor TBX21), encoded by the Tbx21 gene, is a key regulator of T helper 1 (Th1) cell differentiation and cellular immunity. However, the role of T-bet in avian species remains elusive. To investigate the role of T-bet in avian immune response, we cloned chicken T-bet (chT-bet) from a White Leghorn chicken spleen-derived cDNA library. Multiple sequence alignments and structural analyses revealed that the amino acid sequence of chT-bet has 50.4 % and 51.1 % identity to its human and mouse orthologs, respectively, but the T-box DNA-binding domain remains conserved across species. We found that chT-bet is highly expressed in immune-related organs, particularly the spleen and thymus, and that Newcastle disease virus (NDV) infection significantly upregulated chT-bet expression both in virto and in vivo. Knockdown of chT-bet by RNAi markedly reduced the expression of IFN-γ but not IL-4 in MSB1 cells. Furthermore, chT-bet overexpression in DF-1 cells activated the promoter of IFN-γ while suppressing promoter activation of IL-2 and IL-4. Chromatin immunoprecipitation (ChIP) assays confirmed the direct binding of chT-bet to IFN-γ and IL-2 promoters. In contrast, chT-bet′s regulation of IL-4 appeared indirect. These findings establish chT-bet as a central orchestrator of Th1 immunity in chickens, directly driving IFN-γ production and regulating IL-2 and IL-4 expressions through distinct pathways, providing insights for vaccine development and disease control strategies.